THE CONCEPT OF THE SIMULATION MODEL OF THE DECISION SUPPORT SYSTEM OF THE COAL ENTERPRISE - I. S. Bondarenko (Вестник университета)
The article considers the General approach and elements of implementation of the simulation model of the decision support system as one of the most effective ways to improve the management system of a mining enterprise. The paper gives the description of the technological process and the main functional blocks of the control system. The author identifies the key links and requirements for the implementation of the simulation model of production process and enterprise management. The subsystems of the model allow us to consider the dynamics of the production enterprise in all the variety of its activities, for different variants of the technology and organization of production of the existing control system, the planned system and promising management solutions. In addition, the article presents the structure and description of the implemented simulation model of the main production process of the experimental coal mine. The paper indicates the role of the user-manager in the decision-making process based on the results of modeling. The author gives a control example of the simulation results.